2020
DOI: 10.1194/jlr.ra120000924
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance dysregulates CYP7B1 leading to oxysterol accumulation: a pathway for NAFL to NASH transition

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an important public health issue closely associated with the pervasive epidemics of diabetes and obesity. Yet, despite NAFLD being among the most common of chronic liver diseases, the biological factors responsible for its transition from benign nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis (NASH) remain unclear. This lack of knowledge leads to a decreased ability to find relevant animal models, predict disease progression or develop clinical treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 69 publications
6
45
0
Order By: Relevance
“…We hypothesize that a similar mechanism may be occurring in the intestines, whereby the increased bile acid fecal excretion may be due to reduced enterohepatic circulation regulated by SCT/ASBT in the intestines, but this warrants further studies. Parallel with previous findings, ( 50 ) we demonstrated that Cyp7b1 expression was decreased in WT HFD hepatocytes, whereas Sct or Sctr knockout reverses the expression of Cyp7b1 , which indicates that Sct or Sctr knockout alleviates HFD‐induced liver injury by altering the bile acid pathway.…”
Section: Discussionsupporting
confidence: 90%
“…We hypothesize that a similar mechanism may be occurring in the intestines, whereby the increased bile acid fecal excretion may be due to reduced enterohepatic circulation regulated by SCT/ASBT in the intestines, but this warrants further studies. Parallel with previous findings, ( 50 ) we demonstrated that Cyp7b1 expression was decreased in WT HFD hepatocytes, whereas Sct or Sctr knockout reverses the expression of Cyp7b1 , which indicates that Sct or Sctr knockout alleviates HFD‐induced liver injury by altering the bile acid pathway.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, Raselli et al pointed towards a non-essential role of CYP7B1 in MAFLD progression, as both hepatic fibrosis and disease activity score were comparable between HFD-fed WT and Cyp7b1 −/− mice [42]. On the contrary, Kakiyama et al provided evidence that, especially under conditions of insulin resistance, CYP7B1 could mediate progression to steatohepatitis, owing to the accumulation of toxic oxysterols that could promote inflammation and liver damage [43]. Recently, it has been shown that thermoneutral housing, a condition of low brown adipose tissue activity and diminished energy expenditure [44], provides a suitable model of exacerbated diet-induced MAFLD in mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…The serum and liver tissues were processed for bile acid analysis, as described previously [ 19 ]. The processed samples were filtered using Whatman TM Mini-UniPrepTM syringeless filters (0.2 µm PTFE, Cat.…”
Section: Methodsmentioning
confidence: 99%